Pengaruh Literasi Keuangan Teknologi Informasi, Dan Modal Minimal Terhadap Minat Investasi Saham Di Pasar Modal Syariah - Hansen Rusliani; Beid Fitrianova Andriani; Heri Heri (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Analyzing influence of financial literacy, information technology, and minimum capital on interest in investing in shares in the Islamic capital market. Financial literacy (X1) has a significant positive effect on investment interest (Y). Tcount value is 4.156 > Ttable 1.662 and the Sig value is 0.000 < 0.05. Information technology (X2) has a significant positive influence on Investment Interest (Y). Calculated T value of the information technology variable is 6.120 > 1.662 with a significance value of 0.000 < 0.05. Minimum capital (X3) has an insignificant positive influence on investment interest (Y). The T value of the minimum capital variable is 2.812 > 1.662 with a significance value of 0.06 > 0.05. Financial literacy, information technology and minimum capital together have a significant effect on investment interest. Significance values ​​(X1), (X2) and (X3) simultaneously influence (Y) by 0.000 < 0.005 and value of Fcount > Ftable (79.354 > 2.700).